Solid-state battery and method for manufacturing solid-state battery

By introducing a hybrid intermediate layer between the resin current collector and the active material layer, the problem of the active material layer peeling off from the current collector during charging and discharging is solved, thereby improving the cycle characteristics of solid-state batteries, especially the stability of Si-based active materials.

CN119275239APending Publication Date: 2025-01-07TOYOTA JIDOSHA KK
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410868646.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-04
Filing Date
2024-07-01
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

In conventional solid-state batteries, the active material layer can peel off from the current collector during charging and discharging due to expansion or contraction, resulting in reduced cycle performance.

Method used

An intermediate layer is introduced between the resin current collector and the active material layer, in which one component of the active material layer is mixed with one component of the resin current collector to form an intermediate layer, thereby improving the affinity between the two and inhibiting the peeling of the active material layer through the anchoring effect.

Benefits of technology

It effectively suppresses the peeling caused by the expansion and contraction of the active material layer, and improves the cycle characteristics of solid-state batteries, especially when Si-based active materials are included.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275239A_ABST
    Figure CN119275239A_ABST
Patent Text Reader

Abstract

The invention relates to a solid-state battery and a method for manufacturing the solid-state battery. Provided are a solid-state battery and a method for manufacturing the solid-state battery in which deterioration of cycle characteristics is suppressed. A solid-state battery provided with an electrode having: a resin current collector containing a resin and a conductive material; an active material layer containing an active material; and an intermediate layer interposed between the active material layer and the resin current collector, in which at least one component contained in the active material layer is mixed with at least one component contained in the resin current collector.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a solid battery and a method for manufacturing the solid battery. Background Art

[0002] In recent years, secondary batteries such as lithium-ion secondary batteries have been suitably used as portable power sources for personal computers, portable terminals, etc., and as power sources for driving vehicles such as electric vehicles (EV), hybrid vehicles (HV), and plug-in hybrid vehicles (PHV).

[0003] In secondary batteries, since an electrolyte containing a flammable organic solvent is used, a safety device for suppressing the temperature rise during a short circuit needs to be installed, and improvements in the structure and materials for preventing short circuits are required. In contrast, in solid batteries that convert the electrolyte into a solid electrolyte layer and solidify the material, since no flammable organic solvent is used in the battery, the safety device is simplified, and it is believed that the manufacturing cost and productivity are excellent.

[0004] The current collector of a conventional solid battery has a single-layer structure composed of a ceramic foil or a metal foil, or a laminated body including a ceramic foil and a metal foil (for example, Japanese Patent Application Laid-Open No. 2007-329004). Summary of the invention

[0005] Problems to be solved by the invention

[0006] However, in conventional solid batteries including current collectors including ceramic foil and / or metal foil, when the active material layer expands or contracts due to a rapid increase or release of the active material during charge and discharge, the active material layer sometimes peels off from the current collector. As a result, the cycle characteristics (e.g., capacity retention after 50 cycles) sometimes decrease.

[0007] Therefore, in view of the above-mentioned actual situation, an object of the present disclosure is to provide a solid battery and a method for manufacturing a solid battery in which a decrease in cycle characteristics is suppressed.

[0008] Means for solving problems

[0009] Means for solving the above-mentioned problems include the following means.

[0010] <1> A solid battery comprising an electrode, wherein the electrode comprises: a resin collector comprising a resin and a conductive material; an active material layer comprising an active material; and an intermediate layer between the active material layer and the resin collector, in which at least one component contained in the active material layer is mixed with at least one component contained in the resin collector.

[0011] <2> The solid battery according to <1> above, wherein a thickness of the intermediate layer relative to a thickness of the resin collector (intermediate layer / resin collector) is 1 / 30 or more and 1 / 6 or less.

[0012] <3> The solid battery according to <1> or <2> above, wherein the active material includes a Si-based active material.

[0013] <4> The solid battery according to any one of <1> to <3> above, wherein the linear expansion coefficient of the resin current collector is 200×10 -6 ppm / K and above 350×10 -6 Below ppm / K.

[0014] <5> The solid battery according to any one of <1> to <4>, wherein the solid battery includes a solid electrolyte layer including a solid electrolyte, and the softening temperature of the resin is equal to or lower than the crystallization temperature of the solid electrolyte.

[0015] <6> The solid state battery according to any one of <1> to <5>, wherein the conductive material includes vapor grown carbon fiber (VGCF).

[0016] <7> A method for producing a solid battery, comprising the step of pressing a laminated body including a resin collector including a thermoplastic resin and a conductive material and an active material layer including an active material at a temperature not lower than the softening temperature of the thermoplastic resin to produce an electrode.

[0017] Effects of the Invention

[0018] According to the present disclosure, a solid battery and a method for manufacturing a solid battery in which degradation of cycle characteristics is suppressed can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a cross-sectional view showing one embodiment of the solid battery disclosed herein.

[0020] Figure 2 Graph showing the relationship between the constraint pressure variation value and the charge amount in Example 1 and Comparative Example 1.

[0021] Figure 3 Graph showing the relationship between the discharge capacity and the number of charge and discharge cycles in Example 1 and Comparative Example 1.

[0022] Figure 4 Graph showing the relationship between the relative resistance value and the thickness of the intermediate layer in the solid batteries of Example 1, Example 2, and Comparative Example 1.

[0023] Description of Reference Numerals

[0024] A Negative electrode active material layer

[0025] B Solid electrolyte layer

[0026] C Positive electrode active material layer

[0027] 101 Negative electrode active material

[0028] 102 Solid Electrolyte

[0029] 103 Positive electrode active material

[0030] 105, 107 Conductive additives

[0031] 109, 111 Adhesives

[0032] 113 negative electrode collector

[0033] 115 positive electrode collector DETAILED DESCRIPTION

[0034] The following describes an embodiment as an example of the present disclosure. These descriptions and examples are for illustrative purposes only and do not limit the scope of the present disclosure.

[0035] In the present disclosure, a numerical range expressed using "to" means a range including the numerical values ​​described before and after "to" as a lower limit and an upper limit.

[0036] In the numerical range recorded in stages in the present disclosure, the upper limit or lower limit recorded in one numerical range can be replaced by the upper limit or lower limit of the numerical range recorded in another stage. In addition, in the numerical range recorded in the present disclosure, the upper limit or lower limit of the numerical range can be replaced by the value shown in the embodiment.

[0037] In the present disclosure, when a plurality of substances corresponding to each component are present in the composition, the amount of each component in the composition means the total amount of the plurality of substances present in the composition unless otherwise specified.

[0038] In the present disclosure, a combination of two or more preferred aspects is a more preferred aspect.

[0039] In the description of a group (atomic group) in the present disclosure, a description not describing substitution or unsubstitution includes both a case where the group does not contain a substituent and a case where the group contains a substituent.

[0040] In the present disclosure, the term "layer" includes a case where the layer is formed in the entire region when the region where the layer exists is observed, and a case where the layer is formed only in a part of the region.

[0041] In the present disclosure, the term "step" includes not only an independent step but also a step that cannot be clearly distinguished from other steps as long as the intended purpose of the step is achieved.

[0042] -Solid-state battery-

[0043] The solid battery disclosed herein is a solid battery having an electrode, wherein the electrode comprises: a resin collector comprising a resin and a conductive material; an active material layer comprising an active material; and an intermediate layer between the active material layer and the resin collector, in which at least one component contained in the active material layer is mixed (presence of a mixture) with at least one component contained in the resin collector.

[0044] According to the present disclosure, it is possible to suppress a decrease in cycle characteristics (for example, capacity retention rate after 50 cycles). The mechanism of this action is not yet clear, but it is presumed to be as follows.

[0045] The electrode of the solid battery disclosed in the present invention has an intermediate layer between the resin collector and the active material layer. In the intermediate layer, at least one component contained in the active material layer is mixed (mixed) with at least one component contained in the resin collector, so the affinity for both the resin collector and the active material layer is good, and the various components contained in the intermediate layer are mixed, thereby having an anchoring effect. As a result, it is believed that the peeling of the active material layer from the resin collector accompanied by the expansion and contraction of the active material layer during battery driving is suppressed, and the reduction of the cycle characteristics is suppressed.

[0046] Hereinafter, "an electrode having a resin collector comprising a resin and a conductive material; an active material layer comprising an active material; and an intermediate layer between the active material layer and the resin collector, in which at least one component contained in the active material layer is mixed with at least one component contained in the resin collector" will be referred to as a "specific electrode".

[0047] The solid battery disclosed herein includes a so-called all-solid battery using a solid electrolyte as an electrolyte, and the solid electrolyte may also contain less than 10% by mass of an electrolyte relative to the total amount of the electrolyte. Furthermore, the solid electrolyte may be a composite solid electrolyte including an inorganic solid electrolyte and a polymer electrolyte.

[0048] An example of the solid state battery disclosed in the present invention will be described with reference to the drawings. Figure 1 This is a schematic cross-sectional view showing an example of the solid battery of the present disclosure. Figure 1The solid battery shown includes: a negative electrode including a negative electrode collector 113 and a negative electrode active material layer A, a solid electrolyte layer B, and a positive electrode including a positive electrode collector 115 and a positive electrode active material layer C. The negative electrode active material layer A includes a negative electrode active material 101, a conductive auxiliary agent 105, a binder 109, and a solid electrolyte 102. The positive electrode active material layer C includes a positive electrode active material 103, a conductive auxiliary agent 107, a binder 111, and a solid electrolyte 102. The solid electrolyte layer B may be a single layer or a two-layer structure.

[0049] Figure 1 The solid battery shown only needs to include a specific electrode as at least one of the negative electrode and the positive electrode. When the negative electrode is the specific electrode, the negative electrode collector 113 is a resin collector containing a resin and a conductive material. When the positive electrode is the specific electrode, the positive electrode collector 115 is a resin collector containing a resin and a conductive material.

[0050] When the combination (set) of the positive electrode, the solid electrolyte layer and the negative electrode is set as a power generation unit, the solid battery may have only one power generation unit or may have two or more power generation units. When the solid battery has two or more power generation units, these power generation units may be connected in series or in parallel.

[0051] In the case where a solid battery has more than two power generation units (i.e., in the case of a stacked battery), it is sufficient that at least one positive electrode or negative electrode is a specific electrode. From the viewpoint of further suppressing the reduction in cycle characteristics, the electrode located in the middle of the stacked structure is preferably a specific electrode (for example, the "positive electrode active material layer / collector / positive electrode active material layer" and / or the "negative electrode active material layer / collector / negative electrode active material layer" portion of a stacked battery of "negative electrode active material layer / collector / negative electrode active material layer / solid electrolyte layer / positive electrode active material layer / collector / positive electrode active material layer" in the case of a monopolar type, and the "positive electrode active material layer / collector" and / or the "collector / negative electrode active material layer" portion of a stacked battery of "negative electrode active material layer / collector / positive electrode active material layer / solid electrolyte layer / negative electrode active material layer / collector / positive electrode active material layer" in the case of a bipolar type) and the electrodes in all power generation units are preferably specific electrodes.

[0052] The solid battery can seal the stacked end faces (i.e., sides) of the stacked structure of the positive electrode / solid electrolyte layer / negative electrode with a sealing material such as resin. The negative electrode collector 113 and the positive electrode collector 115 can be configured with a buffer layer, an elastic layer, or a PTC (Positive Temperature Coefficient) thermistor layer on the outer peripheral surface.

[0053] The shape of the solid battery is not particularly limited, and may be, for example, a coin shape, a cylinder shape, a square shape, a sheet shape, a button shape, a flat shape, or a stacked shape.

[0054] <Specified Electrode>

[0055] The specific electrode is an electrode having a resin collector containing a resin and a conductive material; an active material layer containing an active material; and an intermediate layer between the active material layer and the resin collector, in which at least one component contained in the active material layer is mixed with at least one component contained in the resin collector.

[0056] The solid battery disclosed herein only needs to include a specific electrode as at least one of the negative electrode and the positive electrode. For example, from the perspective of further suppressing the reduction of cycle characteristics, the solid battery disclosed herein preferably includes a specific electrode as the negative electrode, and more preferably includes a specific electrode as both the negative electrode and the positive electrode.

[0057] [Resin current collector]

[0058] The resin current collector contains a resin and a conductive material.

[0059] As the resin, for example, known thermoplastic resins such as poly(meth)acrylic acid, poly(methyl)acrylate, polyethylene, polypropylene, polyethylene terephthalate, polyether nitrile, polyimide, polyamide, polytetrafluoroethylene, polyacrylonitrile, poly(meth)acrylate, and vinyl halide resins; thermosetting resins such as epoxy resins, vinyl ester resins, unsaturated polyester resins, phenolic resins, and melamine resins; known conductive polymers such as polyaniline, polypyrrole, polythiophene, polyacetylene, polyparaphenylene, polyphenylene vinylene, polyacrylonitrile, and polyoxadiazoles, etc. The resin may be one kind alone or two or more kinds may be used in combination.

[0060] Among them, from the viewpoint of further suppressing the peeling of the active material layer from the resin collector and thus reducing the cycle characteristics, the resin preferably contains at least one of a thermoplastic resin and a conductive polymer, more preferably contains a thermoplastic resin, and further preferably contains a resin selected from polymethyl (meth)acrylate, poly (meth)acrylic acid and polyacrylonitrile.

[0061] In the present disclosure, “(meth)acrylic acid” is a concept including both acrylic acid and methacrylic acid, and “(meth)acrylate” is a concept including both acrylate and methacrylate.

[0062] As for the resin, crystalline resin, amorphous resin and a mixture of the two are all possible. From the viewpoint of improving strength and further inhibiting the active material layer from peeling off from the resin collector, thereby reducing the cycle characteristics, amorphous resin is preferred. It should be noted that the "crystallinity" of the resin refers to an endothermic peak with a half-peak width of less than 10°C when measured at a heating rate of 10°C / min in differential scanning calorimetry (DSC measurement). On the other hand, the so-called "amorphous" of the resin means that the half-peak width exceeds 10°C or no clear endothermic peak is found.

[0063] The softening temperature of the resin varies depending on the type of resin. For example, from the perspective of strength as a resin current collector and the perspective of inhibiting degradation of the active material, the softening temperature of the resin is preferably below the crystallization temperature of the solid electrolyte contained in the solid electrolyte layer described later. It should be noted that the softening temperature of the resin is obtained from a DSC curve obtained by differential scanning calorimetry (DSC).

[0064] Examples of the conductive material include carbon materials, conductive polymers, and metal particles. The conductive material may be used alone or in combination of two or more.

[0065] Examples of carbon materials include particulate carbon materials and fibrous carbon materials. Examples of particulate carbon materials include acetylene black (AB) and Ketjen black (KB). Examples of fibrous carbon materials include carbon nanotubes (CNTs), carbon nanofibers (CNFs), and vapor grown carbon fibers (VGCFs).

[0066] Examples of the conductive polymer include polythiophene, polyacetylene, polyparaphenylene, and polyisothianaphthene.

[0067] Examples of the metal particles include particles of nickel, copper, iron, stainless steel, and the like.

[0068] Among them, from the viewpoint of enhancing the anchoring effect and further inhibiting the peeling of the active material layer from the resin collector, thereby reducing the cycle characteristics, the conductive material preferably contains a carbon material, more preferably contains at least one of acetylene black (AB) and vapor grown carbon fiber (VGCF), and further preferably contains vapor grown carbon fiber (VGCF).

[0069] The content of the conductive material is preferably 10% by mass to 50% by mass, more preferably 15% by mass to 43% by mass, and even more preferably 15% by mass to 35% by mass, based on the total solid content of the resin collector.

[0070] From the viewpoint of further suppressing the active material layer from peeling off from the resin current collector and thus reducing the cycle characteristics, the resin current collector preferably has a linear expansion coefficient of 100×10 -6ppm / K or more and 500×10 -6 ppm / K or less, more preferably 200×10 - 6 ppm / K and above 430×10 -6 ppm / K or less, more preferably 230×10 -6 ppm / K and above 350×10 -6 ppm / K or less. The value of the linear expansion coefficient is a value measured by a method in accordance with JIS H7404-1993.

[0071] The method for making the linear expansion coefficient of the resin current collector fall within the above range is not particularly limited, and examples thereof include a method in which the resin in the resin current collector is made to be the above-mentioned preferred resin.

[0072] There is no particular restriction on the thickness of the resin collector. For example, from the viewpoint of further suppressing the peeling of the intermediate layer and the active material layer from the resin collector and thus reducing the cycle characteristics, the thickness is preferably greater than 5 μm and less than 80 μm, more preferably greater than 10 μm and less than 50 μm, and further preferably greater than 10 μm and less than 30 μm.

[0073] The thickness of the resin collector is determined by observing a stacked cross section cut in the thickness direction of the resin collector using a scanning electron microscope (SEM) equipped with an energy dispersive X-ray spectrometer (EDX), and measuring the average thickness at 10 arbitrary points.

[0074] There is no particular limitation on the method for forming the resin collector, and examples thereof include the following methods: when the resin is thermoplastic, a coating solution containing the resin and the conductive material is applied, dried, and then molded; when the resin is thermosetting, a raw material such as a resin precursor or monomer and the conductive material are placed in a mold, heated, and cured.

[0075] The resin current collector may further contain other materials besides the resin and the conductive material. Examples of other materials include a binder and a metal powder material.

[0076] [Active material layer]

[0077] The active material layer contains an active material. Preferred embodiments of the active material differ depending on whether it is a negative electrode or a positive electrode, and will be described in the respective sections of the negative electrode and the positive electrode described below.

[0078] The active material may include a Si-based active material.

[0079] Si-based active materials are useful active materials with excellent charge and discharge characteristics. However, the expansion and contraction of Si-based active materials associated with charge and discharge tend to be large, so the active material layer is easily peeled off from the collector, and the cycle characteristics are also easily reduced. On the other hand, the solid battery disclosed in the present invention is as described above, because the intermediate layer is between the resin collector and the active material layer in the electrode, the reduction in cycle characteristics caused by the peeling of the active material layer from the resin collector is also suppressed. This is more effective when containing Si-based active materials.

[0080] As the Si-based active material, there is no particular limitation as long as it is a material containing silicon and capable of functioning as an active material, and examples thereof include silicon single-substance particles, silicon alloy particles (e.g., alloys of Si and one or more metals selected from Sn, Ti, Fe, Ni, Cu, Co, and Al), porous silicon, silicon inclusion compounds, silicon oxides, and mixtures thereof, etc. The Si-based active material may be a single type or two or more types may be used in combination.

[0081] There is no particular restriction on the thickness of the active material layer. For example, from the perspective of making the charge and discharge characteristics better and further inhibiting the active material layer from peeling off from the resin collector and thus reducing the cycle characteristics, the thickness is preferably greater than 0.1 μm and less than 100.0 μm, more preferably greater than 1.0 μm and less than 100.0 μm, and further preferably greater than 30.0 μm and less than 100.0 μm.

[0082] The thickness of the active material layer is determined by observing a cross section of the stack cut in the thickness direction of the active material layer using a scanning electron microscope (SEM) equipped with an energy dispersive X-ray spectrometer (EDX), and measuring the average thickness at 10 arbitrary points.

[0083] [Middle layer]

[0084] The intermediate layer is a layer in which at least one component contained in the active material layer and at least one component contained in the resin current collector are mixed.

[0085] From the viewpoint of enhancing the anchor effect and further reducing the separation of the active material layer from the resin current collector, the intermediate layer is preferably a layer in which at least the active material contained in the active material layer and the resin contained in the resin current collector are mixed.

[0086] As for the intermediate layer, from the viewpoint of enhancing the anchoring effect and further reducing the peeling of the active material layer from the resin collector, the thickness of the intermediate layer relative to the thickness of the resin collector (intermediate layer / resin collector) is preferably greater than 1.0 / 30.0 and less than 1.0 / 4.0, more preferably greater than 1.0 / 20.0 and less than 1.0 / 5.0, and further preferably greater than 1.0 / 10.0 and less than 1.0 / 6.0.

[0087] There is no particular restriction on the thickness of the intermediate layer. For example, from the perspective of making the charge and discharge characteristics better and further inhibiting the active material layer from peeling off from the resin collector and thus reducing the cycle characteristics, the thickness is preferably greater than 0.1 μm and less than 15.0 μm, more preferably greater than 0.4 μm and less than 10.0 μm, and further preferably greater than 0.6 μm and less than 8.0 μm.

[0088] The thickness of the intermediate layer is determined by observing a laminate cross section cut in the thickness direction of the intermediate layer using a scanning electron microscope (SEM) equipped with an energy dispersive X-ray spectrometer (EDX), and measuring the average thickness at 10 arbitrary points.

[0089] The components contained in the intermediate layer can be confirmed by performing EDX analysis on the chemical composition of a laminate cross section cut in the thickness direction of the intermediate layer using a scanning electron microscope (SEM) equipped with an energy dispersive X-ray spectrometer (EDX).

[0090] There is no particular limitation on the method for forming the intermediate layer, and for example, the following methods can be cited. 1) When the resin in the resin collector is thermoplastic, a method comprising heating a laminate formed by laminating a resin collector comprising a thermoplastic resin and a conductive material and an active material layer comprising an active material to a temperature above the softening temperature of the thermoplastic resin, and pressing the laminate. 2) When the resin in the resin collector is thermosetting, a method comprising filling a thermosetting resin precursor and components such as an active material and a binder in an active material layer into a mold, and heating the mold to form the laminate.

[0091] The following is a detailed description of the structure of a solid battery including a negative electrode, a positive electrode, and a solid electrolyte layer.

[0092] <Negative electrode>

[0093] The negative electrode is a layer including a negative electrode current collector and a negative electrode active material layer including a negative electrode active material provided on the negative electrode current collector.

[0094] When the negative electrode is a specific electrode, the negative electrode collector corresponds to a resin collector, and an intermediate layer in which at least one component contained in the active material layer and at least one component contained in the resin collector are mixed exists between the active material layer and the resin collector.

[0095] When the negative electrode is not a specific electrode, examples of the material of the negative electrode current collector include stainless steel, copper, nickel, carbon, etc. Examples of the shape of the negative electrode current collector include foil and mesh.

[0096] Examples of the negative electrode active material include carbon materials such as graphite, hard carbon, soft carbon, and carbon nanotubes; and Si-based active materials.

[0097] The negative electrode active material layer may further contain a solid electrolyte, a binder, and the like in addition to the negative electrode active material as necessary.

[0098] Examples of the solid electrolyte include the same substances as those exemplified as the solid electrolyte that can be contained in the solid electrolyte layer.

[0099] As the adhesive, for example, rubber-based adhesives, fluoride-based adhesives, etc. can be listed. As the rubber-based adhesive, for example, butadiene rubber, hydrogenated butadiene rubber, styrene butadiene rubber (SBR), hydrogenated styrene butadiene rubber, nitrile butadiene rubber, hydrogenated nitrile butadiene rubber, ethylene propylene rubber, etc. can be listed. As the fluoride-based adhesive, for example, polyvinylidene fluoride (PVDF), polyvinylidene fluoride-polyhexafluoropropylene copolymer (PVDF-HFP), polytetrafluoroethylene, fluorine rubber, etc. can be listed.

[0100] The mass ratio of the negative electrode active material to the solid electrolyte in the negative electrode (negative electrode active material / solid electrolyte) is not particularly limited, but is preferably, for example, 30 / 70 or more and 85 / 15 or less, and more preferably 40 / 60 or more and 80 / 20 or less.

[0101] <Positive electrode>

[0102] The positive electrode is a layer including, for example, a positive electrode current collector and a positive electrode active material layer including a positive electrode active material provided on the positive electrode current collector.

[0103] When the positive electrode is a specific electrode, the positive electrode collector corresponds to a resin collector, and an intermediate layer in which at least one component contained in the active material layer and at least one component contained in the resin collector are mixed exists between the active material layer and the resin collector.

[0104] When the positive electrode is not a specific electrode, examples of the material of the positive electrode current collector include stainless steel, aluminum, nickel, iron, titanium, carbon, etc. Examples of the shape of the positive electrode current collector include foil and mesh.

[0105] As the positive electrode active material, preferably a lithium composite oxide is included. The lithium composite oxide may contain at least one selected from F, Cl, N, S, Br and I. In addition, the lithium composite oxide may have a crystal structure belonging to at least one space group selected from space groups R-3m, Immm, and P63-mmc (also referred to as P63mc, P6 / mmc.). In addition, the main arrangement of transition metals, oxygen and lithium in the lithium composite oxide may be an O2 type structure.

[0106] Examples of lithium composite oxides having a crystal structure belonging to R-3m include Li x Me y O α X β (Me represents at least one selected from Mn, Co, Ni, Fe, Al, Cu, V, Nb, Mo, Ti, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, Ag, Ru, W, B, Si and P, X represents at least one selected from F, Cl, N, S, Br and I, and satisfies 0.5≤x≤1.5, 0.5≤y≤1.0, 1≤α<2, 0<β≤1.) A compound represented by.

[0107] Examples of lithium composite oxides having a crystal structure belonging to Immm include Li x1 M 1 A 1 2(satisfying 1.5≤x1≤2.3, M 1 Contains at least one selected from Ni, Co, Mn, Cu and Fe, A 1 Contains at least oxygen, A 1 The ratio of oxygen in the composite oxide is 85 atomic % or more. x1 M 1A 1- x2 M 1B x2 O 2-y A 2 y (0≤x2≤0.5, 0≤y≤0.3, at least one of x2 and y is not 0, M 1A represents at least one selected from Ni, Co, Mn, Cu and Fe, M 1B A1 represents at least one selected from Al, Mg, Sc, Ti, Cr, V, Zn, Ga, Zr, Mo, Nb, Ta and W, and A2 represents at least one selected from F, Cl, Br, S and P. ) represents a composite oxide.

[0108] Examples of lithium composite oxides having a crystal structure belonging to P63-mmc include M1 x M2 y A composite oxide represented by O2 (M1 represents an alkali metal (preferably at least one of Na and K), M2 represents a transition metal (preferably at least one selected from Mn, Ni, Co and Fe), and x+y satisfies 0<x+y≤2.).

[0109] Examples of lithium composite oxides having an O2 type structure include Li x [Liα (Mn a Co b M c ) 1-α ]O2 (0.5<x<1.1, 0.1<α<0.33, 0.17<a<0.93, 0.03<b<0.50, 0.04<c<0.33, M represents at least one selected from Ni, Mg, Ti, Fe, Sn, Zr, Nb, Mo, W and Bi.) A composite oxide represented by, as a specific example, Li 0.744 [Li 0.145 Mn 0.625 Co 0.115 Ni 0.115 ]O2, etc.

[0110] In addition, the positive electrode preferably includes a solid electrolyte selected from the solid electrolyte group consisting of a sulfide solid electrolyte, an oxide solid electrolyte, and a halide solid electrolyte in addition to the positive electrode active material, and more preferably at least a portion of the surface of the positive electrode active material is coated with a sulfide solid electrolyte, an oxide solid electrolyte, or a halide solid electrolyte. As the halide solid electrolyte that covers at least a portion of the surface of the positive electrode active material, Li 6-(4-x)b (Ti 1-x Al x ) b F6 (0<x<1, 0<b≤1.5) [LTAF electrolyte].

[0111] The positive electrode may further contain a solid electrolyte, a binder, and the like in addition to the positive electrode active material as necessary.

[0112] As the solid electrolyte, for example, a solid electrolyte containing at least one selected from the group consisting of a sulfide solid electrolyte, an oxide solid electrolyte, and a halide solid electrolyte is preferable.

[0113] The positive electrode preferably has at least a portion of the surface of the positive electrode active material coated with a sulfide solid electrolyte, an oxide solid electrolyte, or a halide solid electrolyte. As the halide solid electrolyte that covers at least a portion of the surface of the positive electrode active material, Li 6-(4-x)b (Ti 1-x Al x ) b F6 (0<x<1, 0<b≤1.5) [LTAF electrolyte].

[0114] Examples of the binder include the same substances as those exemplified as the binder that can be contained in the negative electrode.

[0115] There is no particular restriction on the mass ratio of the positive electrode active material to the solid electrolyte in the positive electrode (positive electrode active material / solid electrolyte), and for example, it is preferably 30 / 70 or more and 90 / 10 or less, more preferably 30 / 70 or more and 85 / 15 or less, and further preferably 50 / 50 or more and 80 / 20 or less.

[0116] <Solid electrolyte layer>

[0117] The solid electrolyte layer contains a solid electrolyte.

[0118] As the solid electrolyte, from the viewpoint of battery performance, it is preferred that at least one solid electrolyte selected from the group consisting of a sulfide solid electrolyte, an oxide solid electrolyte, and a halide solid electrolyte be included, and it is more preferred that a sulfide solid electrolyte be included.

[0119] As a sulfide solid electrolyte, it is preferred to contain sulfur (S) as the main component of the anion element, and preferably contain, in addition to S, for example, Li element and A element. The A element is at least one selected from P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In. The sulfide solid electrolyte may further contain at least one of O and a halogen element. As the halogen element (X), for example, F, Cl, Br, I, etc. can be listed. There is no particular limitation on the composition of the sulfide solid electrolyte, for example, xLi2S·(100-x)P2S5(70≤x≤80), yLiI·zLiBr·(100-yz)(xLi2S·(1-x)P2S5)(0.7≤x≤0.8, 0≤y≤30, 0≤z≤30) can be listed. The sulfide solid electrolyte may have a composition represented by the following general formula (1).

[0120] Li 4-x Ge 1-x P x S4(0<x<1)···Formula (1)

[0121] In formula (1), at least a portion of Ge may be replaced by at least one selected from Sb, Si, Sn, B, Al, Ga, In, Ti, Zr, V and Nb. In addition, at least a portion of P may be replaced by at least one selected from Sb, Si, Sn, B, Al, Ga, In, Ti, Zr, V and Nb. A portion of Li may be replaced by at least one selected from Na, K, Mg, Ca and Zn. A portion of S may be replaced by a halogen. The halogen is at least one selected from F, Cl, Br and I.

[0122] As an oxide solid electrolyte, it is preferred to contain oxygen (O) as the main component of the anion element, for example, it may contain Li, Q element (Q represents at least one of Nb, B, Al, Si, P, Ti, Zr, Mo, W and S.), and O. As oxide solid electrolytes, garnet-type solid electrolytes, perovskite-type solid electrolytes, NASICON-type solid electrolytes, Li-PO-based solid electrolytes, Li-BO-based solid electrolytes, etc. can be listed. As garnet-type solid electrolytes, for example, Li7La3Zr2O 12 , Li 7-x La3(Zr 2-x Nb x ) 12 (0≤x≤2), Li5La3Nb2O 12 Etc. As perovskite-type solid electrolytes, for example, (Li, La)TiO3, (Li, La)NbO3, (Li, Sr)(Ta, Zr)O3, etc. can be cited. As NASICON-type solid electrolytes, for example, Li(Al, Ti)(PO4)3, Li(Al, Ga)(PO4)3, etc. can be cited. As Li-PO-based solid electrolytes, Li3PO4 and LIPON (compounds in which a part of O in Li3PO4 is replaced by N) can be cited. As Li-BO-based solid electrolytes, Li3BO3 and compounds in which a part of O in Li3BO3 is replaced by C can be cited.

[0123] As the halide solid electrolyte, a solid electrolyte containing Li, M and X is preferred (M represents at least one of Ti, Al and Y, and X represents F, Cl or Br). Specifically, Li 6-3z Y z X6 (X represents Cl or Br, z satisfies 0<z<2.), Li 6-(4-x)b (Ti 1-x Al x ) b F6 (0<x<1, 0<b≤1.5). Li 6-3z Y z Among X6, Li3YX6 (X represents Cl or Br) is more preferred from the viewpoint of excellent lithium ion conductivity, and Li3YCl6 is further preferred. In addition, for example, from the viewpoint of suppressing oxidative decomposition of sulfide solid electrolytes, it is preferred to contain Li3YX6 together with solid electrolytes such as sulfide solid electrolytes. 6-(4-x)b (Ti 1-x Al x ) b F6 (0<x<1, 0<b≤1.5).

[0124] The crystallinity of the solid electrolyte varies depending on the type of solid electrolyte used, and is preferably 0% to 90% or less, more preferably 20% to 85% or less, and further preferably 50% to 85% or less. The crystallinity of the solid electrolyte is a value measured by X-ray diffraction.

[0125] <Outer packaging>

[0126] The solid battery may further include an outer package. The outer package contains at least the above-mentioned power generation unit. Examples of the outer package include a stacked outer package, a shell-type outer package, and the like.

[0127] <Constraint components>

[0128] The solid battery may further include a restraining member. The restraining member applies restraining pressure to the positive electrode, the solid electrolyte layer and the negative electrode in the thickness direction. The restraining pressure is preferably 0.1 MPa or more, more preferably 1 MPa or more, and further preferably 5 MPa or more. The restraining pressure is preferably 100 MPa or less, more preferably 50 MPa or less, and further preferably 20 MPa or less. The restraining pressure is preferably 0.1 MPa to 100 MPa.

[0129] <Application>

[0130] The solid battery disclosed in the present invention is typically a solid secondary battery (more preferably a solid lithium ion secondary battery). As the use of the solid battery, power sources such as vehicles, electronic devices, and electrical storage can be listed. As vehicles, electric four-wheeled vehicles, electric two-wheeled vehicles, gasoline vehicles, diesel vehicles, etc. can be listed. As electric four-wheeled vehicles, for example, electric vehicles (BEV), plug-in hybrid vehicles (PHEV), and hybrid electric vehicles (HEV) can be listed. As electric two-wheeled vehicles, for example, electric motorcycles and electric power-assisted bicycles can be listed. As electronic devices, handheld devices (such as smart phones, tablet computers, audio players, etc.), portable devices (such as laptops, CD (Compact Disc) players, movable devices (such as power tools, business cameras, etc.) can be listed. Among them, the use of the solid battery disclosed in the present invention is preferably a driving power source for hybrid vehicles, plug-in hybrid vehicles or electric vehicles.

[0131] -Method for manufacturing solid state battery-

[0132] The present disclosure provides a method for manufacturing a solid battery, including the step of pressing a laminated body including a resin collector including a thermoplastic resin and a conductive material and an active material layer including an active material at a temperature not lower than the softening temperature of the thermoplastic resin to produce an electrode.

[0133] In the case of the manufacturing method of the solid battery involved in the present disclosure, for example, by pressing the above-mentioned laminate above the softening temperature of the thermoplastic resin, the active material layer intrudes into the area where the thermoplastic resin in the resin collector is softened, and an intermediate layer in which at least one component contained in the active material layer and at least one component contained in the resin collector are mixed is formed between the active material layer and the resin collector. The intermediate layer has good affinity with both the resin collector and the active material layer, and the various components contained in the intermediate layer have an anchoring effect. As a result, it is believed that the peeling of the active material layer from the resin collector accompanied by the expansion and contraction of the active material layer during battery driving is suppressed, and the reduction of the cycle characteristics is suppressed.

[0134] The manufacturing method of the solid battery involved in the present disclosure may be, for example, the following manufacturing method, which includes: a process of pressing a stack formed by stacking a resin collector containing a thermoplastic resin and a conductive material and an active material layer containing an active material above the softening temperature of the thermoplastic resin to produce an electrode (hereinafter also referred to as the "electrode manufacturing process"); and a process of stacking the electrode serving as at least one of the positive electrode and the negative electrode and a solid electrolyte layer to obtain a solid battery (hereinafter also referred to as the "stacking process").

[0135] <Electrode production process>

[0136] In the electrode manufacturing step, a laminated body including a resin collector containing a thermoplastic resin and a conductive material and an active material layer containing an active material is pressed at a temperature not lower than the softening temperature of the thermoplastic resin to manufacture an electrode.

[0137] Preferred embodiments of the resin current collector comprising a thermoplastic resin and a conductive material are the same as those in the above-mentioned solid battery section. Preferred embodiments of the active material layer comprising an active material are the same as those in the above-mentioned solid battery section.

[0138] The softening temperature of the thermoplastic resin varies depending on the thermoplastic resin used, and may be, for example, 100° C. to 200° C., 110° C. to 190° C., or 130° C. to 180° C.

[0139] The heating temperature of the laminate only needs to be above the softening temperature of the thermoplastic resin. From the viewpoint of battery performance, the viewpoint of more efficiently forming the intermediate layer, etc., it is preferably above the softening temperature of the thermoplastic resin and below the softening temperature+100°C, preferably above the softening temperature and below the softening temperature+90°C, more preferably above the softening temperature and below the softening temperature+80°C, and further preferably above the softening temperature and below the softening temperature+75°C.

[0140] There is no particular limitation on the method for pressing the laminate, and the laminate may be pressed while being heated above the softening temperature of the thermoplastic resin (i.e., heating and pressing may be independent processes), or may be pressed while being heated above the softening temperature of the thermoplastic resin (i.e., heating and pressing may be simultaneous processes). As for the method for pressing the laminate, from the viewpoint of manufacturing efficiency, it is preferred to press while heating the laminate above the softening temperature of the thermoplastic resin.

[0141] As a pressing method, for example, roll pressing, cold isostatic pressing (CIP), etc. The pressing pressure is not particularly limited as long as the active material layer penetrates the resin collector to form an intermediate layer, and can be 1 kN / cm or more and 100 kN / cm or less, 5 kN / cm or more and 80 kN / cm or less, or 10 kN / cm or more and 70 kN / cm or less.

[0142] <Lamination process>

[0143] In the stacking step, the electrode as at least one of a positive electrode and a negative electrode and a solid electrolyte layer are stacked to obtain a solid battery.

[0144] The electrode produced in the above-mentioned electrode production step can be used in either the positive electrode or the negative electrode. For example, from the viewpoint of further suppressing the reduction in cycle characteristics, it is preferred to have the electrode produced in the above-mentioned electrode production step as the negative electrode, and it is more preferred to have the electrode as both the negative electrode and the positive electrode.

[0145] Preferred embodiments of the solid electrolyte layer are the same as those in the above-mentioned preferred embodiments of the solid battery. As a method of laminating the electrode and the solid electrolyte layer, a known method can be applied.

[0146] <Other Process>

[0147] The manufacturing method of the solid battery disclosed in the present invention may further include other processes besides the electrode manufacturing process and the lamination process. As other processes, for example, the process of initially charging the solid battery; the process of making the solid battery into a bipolar solid battery; the process of processing into a predetermined size by cutting, punching, etc.; the process of laminating the solid battery, etc. can be listed.

[0148] Example

[0149] <Example 1>

[0150] [Production of positive electrode]

[0151] The NCA-based positive electrode active material (LiNi 0.8 Co 0.15 Al 0.05The positive electrode composite material of NCA-based positive electrode active material: sulfide-based solid electrolyte: vapor-grown carbon fiber: PVdF-based binder in the positive electrode slurry was stirred with an ultrasonic dispersion device to prepare a positive electrode slurry. The mass ratio of NCA-based positive electrode active material: sulfide-based solid electrolyte: vapor-grown carbon fiber: PVdF-based binder in the positive electrode slurry was adjusted to 88.2:9.8:1.3:0.7. The positive electrode slurry was applied to Al foil and SUS foil respectively by a doctor blade method, and these were dried on a hot plate at 100°C for 30 minutes to obtain two positive electrodes with positive electrode active material layers.

[0152] [Production of negative electrode]

[0153] The negative electrode composite material containing powdered Si particles as raw materials, sulfide-based solid electrolyte (Li2S-P2S5), conductive material (VGCF), PVDF-based binder and butyl butyrate was stirred using an ultrasonic dispersion device to prepare a negative electrode slurry. The mass ratio of powdered Si particles: sulfide-based solid electrolyte: carbon material: PVDF-based binder in the negative electrode slurry was adjusted to 100:77.6:2:15. The negative electrode slurry was applied to Ni foil and SUS foil respectively using a doctor blade method, and these were dried on a hot plate at 100°C for 30 minutes to obtain two negative electrodes with negative electrode active material layers.

[0154] [Fabrication of Solid Electrolyte Layer]

[0155] A solid electrolyte composite material containing a sulfide-based solid electrolyte (Li2S-P2S5) as a raw material, a PVDF-based binder and butyl butyrate was stirred using an ultrasonic dispersion device to prepare a solid electrolyte slurry. The solid electrolyte slurry was adjusted in such a way that the mass ratio of the sulfide-based solid electrolyte: PVDF-based binder was 99.4:0.4. The solid electrolyte slurry was applied to each positive electrode active material layer of the two positive electrodes prepared above using a doctor blade method, and a stack of solid electrolyte layer / positive electrode active material layer / Al foil (solid electrolyte layer / positive electrode) and a stack of solid electrolyte layer / positive electrode active material layer / SUS foil (solid electrolyte layer / positive electrode) were obtained, respectively.

[0156] [Production of Resin Current Collector]

[0157] A conductive paste obtained by mixing the conductive materials of the types and amounts shown in Table 1, polymethyl methacrylate (amorphous resin) as a resin, and butyl butyrate was coated on a PET film by a doctor blade method, and after drying at 150° C. for 30 minutes, the PET film was peeled off to obtain a resin current collector. In addition, the glass transition temperature (i.e., softening temperature) of the resin is less than the crystallization temperature of the solid electrolyte.

[0158] [Production of Laminated Body]

[0159] The two types of positive electrode / solid electrolyte layers and the two types of negative electrodes prepared above were stacked in the following combinations to obtain two pseudo-stacks.

[0160] ·Ni foil / negative electrode active material layer / solid electrolyte layer / positive electrode active material layer / SUS foil

[0161] ·SUS foil / negative electrode active material layer / solid electrolyte layer / positive electrode active material layer / Al foil

[0162] Next, the two quasi-laminates are respectively pressed by a roller press at a pressing pressure of 50 kN / cm and a temperature of 160°C. Then, the SUS foils are peeled off from the quasi-laminates, and a resin collector is arranged between the laminates from which the SUS foils are peeled off, and the laminates are stacked to obtain a laminate having a laminate structure of "Ni foil / negative electrode active material layer / solid electrolyte layer / positive electrode active material layer / resin collector / negative electrode active material layer / solid electrolyte layer / positive electrode active material layer / Al foil". Then, the laminate is pressed by a roller press at a pressing pressure of 20 kN / cm and a temperature of 160°C. Next, cut into 1 cm 2 size, thereby obtaining a solid battery with a stacked structure of "Ni foil / negative electrode active material layer / solid electrolyte layer / positive electrode active material layer / intermediate layer / resin collector / intermediate layer / negative electrode active material layer / solid electrolyte layer / positive electrode active material layer / Al foil".

[0163] <Example 2 to Example 7>

[0164] A resin collector was obtained in the same manner as in Example 1 except that the amount of resin, the type and amount of conductive material were as shown in Table 1. A solid battery was obtained in the same manner as in Example 1 except that the obtained resin collector was used.

[0165] <Comparative Example 1>

[0166] [Production of positive electrode]

[0167] The NCA-based positive electrode active material (LiNi 0.8 Co0.15 Al 0.05 The positive electrode material of NCA positive electrode active material: sulfide solid electrolyte: vapor phase growth carbon fiber: PVdF binder in the positive electrode slurry is 88.2:

[0168] The positive electrode slurry was applied onto an Al foil by a doctor blade method and dried on a hot plate at 100° C. for 30 minutes to obtain a positive electrode having a positive electrode active material layer.

[0169] [Production of negative electrode]

[0170] The negative electrode composite material including powdered Si particles as raw materials, sulfide-based solid electrolyte (Li2S-P2S5), conductive material (VGCF), PVDF-based binder and butyl butyrate was stirred using an ultrasonic dispersion device to prepare a negative electrode slurry. The mass ratio of powdered Si particles: sulfide-based solid electrolyte: carbon material: PVDF-based binder in the negative electrode slurry was adjusted to 100:77.6:2:15. The negative electrode slurry was applied to Ni foil using a doctor blade method and dried on a hot plate at 100°C for 30 minutes to obtain a negative electrode with a negative electrode active material layer.

[0171] [Fabrication of Solid Electrolyte Layer]

[0172] A solid electrolyte composite material containing a sulfide-based solid electrolyte (Li2S-P2S5) as a raw material, a PVDF-based binder, and butyl butyrate was stirred using an ultrasonic dispersion device to prepare a solid electrolyte slurry. The solid electrolyte slurry was adjusted in such a way that the mass ratio of the sulfide-based solid electrolyte: PVDF-based binder was 99.4:0.4. The solid electrolyte slurry was applied to the positive electrode active material layer of the positive electrode prepared above using a doctor blade method to obtain a laminate of solid electrolyte layer / positive electrode active material layer / Al foil (solid electrolyte layer / positive electrode).

[0173] [Production of Laminated Body]

[0174] The positive electrode / solid electrolyte layer and the negative electrode prepared above were stacked to form the following combination to obtain a stacked body.

[0175] Ni foil / negative electrode active material layer / solid electrolyte layer / positive electrode active material layer / Al foil

[0176] Next, the laminate was pressed with a roll press at a pressing pressure of 50 kN / cm and a temperature of 160° C. Next, the laminate was punched out into 1 cm 2 size, thereby obtaining a solid battery having a stacked structure of “Ni foil / negative electrode active material layer / solid electrolyte layer / positive electrode active material layer / Al foil”.

[0177] <Comparative Example 2>

[0178] A solid battery was obtained in the same specifications as in Example 1 except that the laminate was pressed at a pressing pressure of 20 kN / cm at 25° C. using a roll press without heating.

[0179] <Comparative Example 3>

[0180] A solid battery was obtained with the same specifications as in Example 1 except that the temperature when the stack was heated and pressed (represented as "pressing temperature" in the table) was set to the specifications shown in Table 1 (i.e., a temperature lower than the softening temperature of polymethyl methacrylate).

[0181] The thickness of each active material layer, intermediate layer, and resin collector in the "positive electrode active material layer / intermediate layer / resin collector / intermediate layer / negative electrode active material layer" of the solid battery of each example was measured by the above method. The results are shown in Table 1. In addition, for the solid batteries of Comparative Examples 2 and 3, it can be seen from the results of the measurement using the above method that there is no intermediate layer.

[0182] In Table 1, the item "thickness ratio (intermediate layer / resin current collector)" refers to the thickness of the intermediate layer relative to the thickness of the resin current collector (intermediate layer / resin current collector).

[0183] <Evaluation of charging limit pressure>

[0184] The solid batteries of Example 1 and Comparative Example 1 were clamped between two restraining plates, and the two restraining plates were fastened with a fastener at a restraining pressure of 5 MPa to fix the distance between the two restraining plates. Next, the restrained stack was charged at a constant current of 1 / 10C until 8.10V, and then charged at a constant voltage of 8.10V until the termination current was 1 / 100C. Then, the restraining pressure before and after charging was recorded. The restraining pressure P before charging was recorded. 之前 The constraint pressure P at the end of charging 之后 The difference (P 之前 -P 之后 The value obtained by dividing the absolute value of ) by the discharge capacity is defined as the constraint pressure variation value. The larger the constraint pressure variation value, the greater the expansion of the solid battery associated with charging.

[0185] Figure 2 Graph showing the relationship between the constraint pressure variation value and the charge amount in Example 1 and Comparative Example 1. Figure 2 As shown, the solid battery of Example 1 suppresses the fluctuation of the confinement pressure accompanying charging as compared with the solid battery of Comparative Example 1.

[0186] <Evaluation of discharge capacity>

[0187] Using a galvanometer, 50 cycles of charge and discharge tests were performed under the conditions of a current of 0.1C, a charge termination voltage of 8.10V, and a discharge termination voltage of 5.0V. Starting from charging, after completing one charge, the current required for discharge to 5.0V was calculated and divided by the weight of the active material used in the measurement to calculate the discharge capacity in each cycle. Then, the 50th discharge capacity was divided by the first discharge capacity to obtain the capacity retention rate (%) after 50 cycles. The results are shown in Table 1.

[0188] Figure 3 Graph showing the relationship between the discharge capacity and the number of charge and discharge cycles in Example 1 and Comparative Example 1. Figure 3 As shown, it can be seen that the solid battery of Example 1 is superior to the solid battery of Comparative Example 1 in capacity retention, that is, the decrease in cycle characteristics is suppressed.

[0189] <Evaluation of resistance value>

[0190] The solid batteries of Example 1, Example 2 and Comparative Example 1 are clamped between two restraining plates, and the two restraining plates are fastened with a restraining pressure of 5MPa using fasteners to fix the distance between the two restraining plates. Secondly, the constrained stack is charged with a constant current of 1 / 10C to 8.10V, and then, it is charged with a constant voltage of 8.10V to a termination current of 1 / 100C. Then, a constant current discharge of 1 / 10C to 5.0V is performed, and then, a constant voltage discharge of 5.0V to a termination current of 1 / 100C is performed. Then, the absolute value of the difference between the voltage before charging and the voltage after 0.1 second discharge is divided by the current equivalent to 1 / 100C to calculate the resistance value. The relative value of the obtained resistance value to the resistance value in the solid battery of Comparative Example 1 is shown in Figure 4 .

[0191] Figure 4 Graph showing the relationship between the relative resistance value and the thickness of the intermediate layer in the solid batteries of Example 1, Example 2 and Comparative Example 1. Figure 4 As shown, it can be seen that the solid battery of Example has suppressed the increase in resistance value due to the separation of the active material layer from the current collector, as compared with the solid battery of Comparative Example 1.

[0192]

[0193] As shown in Table 1, it can be seen that the solid battery of the example is superior in capacity retention rate, that is, the decrease in cycle characteristics is suppressed, as compared with the solid battery of the comparative example.

Claims

1. A solid battery comprising an electrode, wherein the electrode comprises: a resin current collector comprising a resin and a conductive material; an active substance layer comprising an active substance; and An intermediate layer is interposed between the active material layer and the resin current collector, in which at least one component contained in the active material layer and at least one component contained in the resin current collector are mixed.

2. The solid battery according to claim 1, wherein: The thickness of the intermediate layer relative to the thickness of the resin collector (intermediate layer / resin collector) is 1 / 30 or more and 1 / 6 or less.

3. The solid battery according to claim 1 or 2, wherein: The active material includes a Si-based active material.

4. The solid battery according to claim 1 or 2, wherein: The linear expansion coefficient of the resin collector is 200×10 -6 ppm / K and above 350×10 -6 Below ppm / K.

5. The solid battery according to claim 1 or 2, wherein: The solid battery includes a solid electrolyte layer including a solid electrolyte, and the softening temperature of the resin is equal to or lower than the crystallization temperature of the solid electrolyte.

6. The solid battery according to claim 1 or 2, wherein: The conductive material includes vapor grown carbon fiber (VGCF).

7. A method for manufacturing a solid battery, comprising the steps of: pressing a laminated body formed by laminating a resin collector containing a thermoplastic resin and a conductive material and an active material layer containing an active material at a temperature above the softening temperature of the thermoplastic resin to produce an electrode.

Citation Information

Patent Citations

  • Electrode for bipolar battery

    JP2007329004A